2014
DOI: 10.3389/fmicb.2014.00417
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Salmonella strains from the SARA, SARB and SARC reference collections by using three genes PCR-RFLP and the 2100 Agilent Bioanalyzer

Abstract: Rapid molecular typing methods are important tools in surveillance and outbreak investigations of human Salmonella infections. Here we described the development of a three-genes PCR-RFLP typing method for the differentiation of Salmonella species, subspecies and serovars using the Agilent 2100 Bioanalyzer. The fliC, gnd, and mutS genes were PCR-amplified in 160 Salmonella strains representing the two Salmonella species, six subspecies, and 41 different serovars of S. enterica subspecies enterica. PCR products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Each RT-PCR primer pair is provided with a positive control. For more precise quantification, targeted PCR reactions were carried out, and the amplified products were analyzed by automated chip-based microcapillary electrophoresis on an Agilent 2100 Bioanalyzer instrument (Agilent Technologies, Santa Clara, CA) as previously described 52 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Each RT-PCR primer pair is provided with a positive control. For more precise quantification, targeted PCR reactions were carried out, and the amplified products were analyzed by automated chip-based microcapillary electrophoresis on an Agilent 2100 Bioanalyzer instrument (Agilent Technologies, Santa Clara, CA) as previously described 52 53 .…”
Section: Methodsmentioning
confidence: 99%
“…The experimental approach using Pma CI confirmed that the in silico pattern produced in P. salmonis was distinguishable to the pattern generated in co-habitant bacteria, validating our prediction (Figure 2 ). Additionally, since the technique involves an enzymatic amplification of the 16S rDNA gene, its detection limit is comparable with all other PCR-based methods used to detect P. salmonis in agarose gels, whereas its visualization is widely improved (0.25 ng, 1000-fold improved) using the ScreenTapes of TapeStation 2200 technology, as it has been reported recently (Soler-García et al, 2014 ). Moreover, the development of new ScreenTapes (high sensitivity D5000 of Agilent Technologies) promises to further improve this detection limit to 0.01 ng, which will give remarkable sensibility to all PCR based methods, including our PCR-RFLP assay.…”
Section: Discussionmentioning
confidence: 75%
“…The resolution of bands was further improved by the use of Agilent Bioanalyzer. In the present investigation band profiles with high quality sizing resolution (1000–7500 bp: 15%), sizing accuracy (± 10% CV) and sizing reproducibility (5% CV) were obtained, which are essential requirements in fingerprinting based differentiation [ 51 , 52 ]. In our study, the Agilent Bioanalyzer’s band profiles along with the most advanced version of BioNumerics 7.5 formed a model experiment-analysis combination.…”
Section: Discussionmentioning
confidence: 99%